Interaction Patterns of Lecturer and Student in Online Lectures in Introduction to Linguistic Course - Rusdiah Rusdiah; Rizkariani Sulaiman (Jurnal Sinestesia, 2023)
The lecture system on campus has undergone changes to adapt to new-normal conditions. Previously, lectures were carried out face-to-face as a whole, currently lectures are carried out using blended learning by combining face-to-face and online meetings. It is urgent to study online lectures because various challenges arise from both lecturers and students in their implementation. The aim of this research is to determine the interaction patterns of lecturers and students in online lectures in the Introduction to Linguistics course. This research uses qualitative methods, especially conversation analysis. The research will be carried out in the English Literature study program, Faculty of Letters, UMI, with research subjects being one English Literature lecturer, Faculty of Letters, Indonesian Muslim University, who teaches the Introduction to Linguistics course and class C1 students consisting of 32 students. Data in this research will be collected using audio/video recordings and interviews and analyzed using the IRF and FLINT models. The results of the research show that the IRF (Initiation, Response, Feedback) interaction pattern consists of complete IRF patterns of eighty-two (82) frequencies or 76.63%, IR which is a semi-complete pattern of 25 frequencies or 23.37% and none IF or incomplete patterns were identified starting from video transcripts of meetings one to five. Meanwhile, based on identification according to the FLINT model from video transcripts 1 to video 5, the dominant one is providing information, namely 71 frequencies (25.08%), then giving directions 68 frequencies (24.02%), giving questions 54 frequencies (19.08%), providing encouragement to increase student self-confidence 41 frequency (14.48%), facilitating student ideas 37 frequency (13.07%), conveying corrections 7 frequency (2.47%), accommodating student feelings 5 frequency (1.76% ), and no interaction was found in the form of criticism of student behavior.